Intensification of agriculture on Vertisols to minimize land degradation in parts of the Ethiopian highlands - El Wakeel, A.; Astatke, A. (Wiley, 1996)
This paper highlights some interventions which might alleviate agricultural pressures on steep slopes and reduce land degradation in parts of the Ethiopian Highlands. The Ethiopian highlands are losing alarming amounts of soils (estimated at more than one billion, 1000 million, tonnes) annually. This loss, which is associated with nutrient losses, is manifest in declining agricultural production and biodiversity. About 80 percent of the annual soil loss occurs from croplands during the rainy season. The nutrient imbalance is further accentuated by forest clearing, removal of crop residue from cultivated lands, and little use of chemical fertilizers or organic manure. Even where livestock are part of the production system, dung is preferentially used as a cooking fuel. Chemical fertilizers are costly, and therefore an alternative land-management scheme is suggested. This is based on a new land-shaping device for drainage which is called the BBM (broad-bed maker), and growing forage legumes to improve soil nutrients, which should allow intensive cultivation of Vertisols in the Ethiopian Highlands. Adoption of the broad bed and furrow land-management system would facilitate early planting and increase the yield of both grain and straw from the major crops relative to the yield from traditional cultivation in flat beds. While not decreasing the yield of grain, mixed cropping of grain and forage crops has been shown to give significantly greater total crop residue yields. The yield is even greater when fertilizers are applied. Supplementary irrigation can help in utilizing Vertisols on bottom lands, and this can be expedited by constructing water reservoirs.